Pengaruh Label dan Influencer Endorsement Terhadap Keputusan Pembelian Air Minum Dalam Kemasan (AMDK) Merek Le Minerale Pada Generasi Z di Kota Mataram - Rahmawati, Dini Sari; Retnowati, Weni (Postgraduate, University of Mataram, 2025)
This study aims to examine the influence of product labels and influencer endorsements on the purchase decisions of bottled drinking water (AMDK) brand Le Minerale among Generation Z in Mataram City. The research method used is a quantitative approach with an associative research type. The sample size involved 100 respondents, determined thru a non-probability sampling method using the purposive sampling technique. Data analysis was performed using multiple linear regression to test the hypothesis, with the assistance of SPSS version 25 software. The research results indicate that the product label variable has a positive and significant effect on purchasing decisions with a calculated t-value of 6.711 > t-table 1.984 and a significance of 0.000 < 0.05. Similarly, the influencer endorsement variable has a positive and significant effect on purchasing decisions with a calculated t-value of 2.362 > t-table 1.984 and a significance of 0.020 < 0.05. Therefore, it can be concluded that both product labels and influencer endorsements have a real contribution to influencing the purchase decisions of Le Minerale brand AMDK among Generation Z in Mataram City.